The Role of Community-Based Accountability and Social Accounting Practices in Enhancing Community Welfare: Evidence from Local Community Organizations in Indonesia - Muhammad Fajeri Siregar; Muhammad Hafis Akbar Nasution; Emi Uliyanty Boru Sidabutar; Veranda Panjaitan; Jenny Ester Pandiangan (Golden Ratio of Community Services and Dedication, 2026)
This study examines the role of community-based accountability and social accounting practices in enhancing community welfare through local community organizations in Indonesia. It aims to explain how transparent governance, community participation, responsiveness, social-impact measurement, and public reporting contribute to inclusive and sustainable welfare outcomes. The study employs a qualitative literature review by synthesizing peer-reviewed journal articles, conference proceedings, and institutional reports concerning nonprofit accountability, village institutions, community organizations, social accounting, and welfare development. The selected literature was analyzed thematically to identify recurring concepts, empirical patterns, institutional challenges, and emerging research directions. The results show that community-based accountability improves organizational legitimacy and program relevance when it extends beyond administrative compliance and enables beneficiaries to influence planning, monitoring, evaluation, and corrective action. Social accounting strengthens this process by connecting financial resources and organizational activities with outcomes such as livelihood improvement, service accessibility, empowerment, social inclusion, trust, and social cohesion. The principal finding is that accountability and social accounting function most effectively as complementary mechanisms rather than independent practices. Their contribution to welfare depends on managerial competence, accessible information, meaningful participation, digital capacity, and institutional responsiveness. The study highlights the need for participatory, context-sensitive, and digitally supported accountability systems within Indonesian local organizations.